2021
DOI: 10.1002/essoar.10509492.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hestia-AKL: An Inventory of Fossil Fuel CO<sub>2</sub> Emissions for Auckland, New Zealand

Abstract: The largest city in New Zealand, Auckland is home to roughly 1.5 million people -one third of New Zealand's population.Here we assemble a bottom-up inventory of Auckland's fossil fuel carbon dioxide emissions from a variety of data sources. We use these emissions estimates in combination with the UrbanVPRM land surface model to estimate the net carbon balance of the region. This work is part of the larger CarbonWatch NZ project, which aims to produce estimates of New Zealand's net carbon balance quickly enough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…While this is often used to estimate CO 2 production, bottom-up methods are accompanied by a significant degree of uncertainty. More importantly, it can be difficult to accurately quantify uncertainties, often leading to less reliable results [Gurney et al, 2021]. In Gurney et al [2021], self-reported inventories (SRIs) from US cities underestimated emissions by almost 20% on average, with SRI values ranging from a -145% to 63% difference from the Vulcan model [Gurney et al, 2020].…”
Section: Thesis Outlinementioning
confidence: 99%
See 2 more Smart Citations
“…While this is often used to estimate CO 2 production, bottom-up methods are accompanied by a significant degree of uncertainty. More importantly, it can be difficult to accurately quantify uncertainties, often leading to less reliable results [Gurney et al, 2021]. In Gurney et al [2021], self-reported inventories (SRIs) from US cities underestimated emissions by almost 20% on average, with SRI values ranging from a -145% to 63% difference from the Vulcan model [Gurney et al, 2020].…”
Section: Thesis Outlinementioning
confidence: 99%
“…More importantly, it can be difficult to accurately quantify uncertainties, often leading to less reliable results [Gurney et al, 2021]. In Gurney et al [2021], self-reported inventories (SRIs) from US cities underestimated emissions by almost 20% on average, with SRI values ranging from a -145% to 63% difference from the Vulcan model [Gurney et al, 2020]. The Vulcan model is a US inventory emissions model created from a range of publicly available emission data which has been shown to be in good agreement with flask measurements [Gurney et al, 2021].…”
Section: Thesis Outlinementioning
confidence: 99%
See 1 more Smart Citation